Shareholder Wealth Effect and Payment Method in Domestic M&As Transactions: Evidence from the US and Asia Emerging Market - Li, Boya (2014)
This paper employs the empirical methodology to investigate the impacts of M&As on shareholder wealth and the relationship between firm value and payment choice. Furthermore, it also intends to recognize some important determinants of payment choice. Most of theories have only been examined in developed economies. However, the studies in developing countries are still insufficient. That is due to the reason that comprehensive database and the number of transactions is shortage in developing countries. Therefore, it begs the question of whether the evidence found in a developed country is equally suitable for the emerging market. In general, the empirical results are in accordance with the previous study. For instance, the shareholder will obtain negative or around zero return from M&As in the US market, while the merger deal would create a significant positive return for acquiring shareholders in Asia emerging market. In addition, the cash offer can generate higher abnormal return compared with stock offer in both markets. However, different with most of the studies, the conclusion in the Asia market suggests that stock-financed acquisition will also generate positive returns which may be due to the centralized shareholder structure. Because of the different characteristics in these two markets, the investigation illustrates that the determinants which are significant in the US market lose their explanatory power in the Asia emerging market.